Evaluation of awake burr hole drainage for chronic subdural hematoma in geriatric patients: a retrospective analysis of 3 years - Albayrak, Serdal; Atci, Ibrahim Burak; Ucler, Necati; Yilmaz, Hakan; Kaplan, Metin (Cukurova Univ, Fac Medicine, 2016)
Purpose: The goal of this research was to evaluate the effectiveness of burr hole drainage under local anesthesia in geriatric patients with chronic subdural hematoma. Material and Methods: This retrospective study involved 21 geriatric patients with chronic subdural hematoma who applied to the department of neurosurgery in an education and research hospital between 2011 and 2014. Sedoanalgesia was performed on 21 patients, then awake burr hole drainage was performed after scalp and periosteal local anesthesia with bupivacaine HCI 5mg/ml (Marcaine %0,5enj. Astrazeneca). Cranial motor perforator was used for burr hole trepanation. Age, sex, trauma history, examination findings, site of the pathology, systemic disease, ASA risk, glasgow coma scale, modified rankin scale, mortality and morbidity were evaluated. Results: The youngest patient was 68-year-old, the oldest was 90-year-old. The average age was 72.9 years. Eleven of the cases were male and 10 were female. Head trauma was the etiology in 20 cases. 2 burr hole drainages were performed in 18 cases and 1 burr hole drainage was performed in 3 cases under local anesthesia. 3 cases were re-operated. No mortality was seen in the early postoperative period. Cases were kept in the intensive care unit for 1 day. The average hospital stay was 7 days. Conclusion: Surgical interventions under local anesthesia in geriatric patients with chronic subdural hematoma can provide short operation time, early mobilization, early oral intake, avoidance of possible general anesthesia complications. Herewith, this intervention decrease mortality and morbidity in this age group.
Keywords: Burr hole drainage; subdural hematoma